(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
Syria is one of the countries that assented the Biodiversity convention since 1995, and was very interested in this field .Syria also made a big improvement in a short period of time. The present study is stepping that enrichment of Crustaceans Biodiversity in general and terrestrial isopods (woodlice )in particular. The specimens of terrestrial isopods were collected randomly from different regions in Lattakia ( Tishreen University gardens, Olive fields of Wadi Kandeel, Al Surskya, Khorbit Al Gauzia, Berna ,Kesmin ,Ain Albida , Alshmia and Supralittoral Zone of Ibn Hani and City Sport ), during 2015-2018. After the treatment of specimens, Six species from terrestrial Isopods were identified; five is these for the first time in Syria. These species are: Armadillidium vulgare; Armadillo officinalis , Porcellio laevis Porcelliondes pruinosus; Ligia italica. ; P. scaber The species were morphologically described .The inhabitance of these species was accorded to environmental factors which affect their distribution such as temperature and humidity. تعد سورية من الدول التي صادقت على اتفاقية التنوع الحيوي عام 1995م وبدأت بالاهتمام الكبير بهذا الموضوع وحققت الكثير من الانجازات خلال فترة قصيرة والدراسة الحالية هي خطوة في رسم خارطة التنوع الحيوي للقشريات عموماً والبرية خاصة. جمعت عينات القشريات متماثلات الأرجل البرية عشوائياً خلال الأعوام 2015- 2018 م من مناطق مختلفة من اللاذقية ( حدائق جامعة تشرين وبساتين الزيتون في وادي قنديل والسرسكية وخربة الجوزية وقرى برنة وقسمين وعين البيضا والشامية وغيرها، ومن المنطقة فوق الشاطئية لمنطقة إبن هاني والمدينة الرياضية. وقد نتج عن معالجة هذه العينات تسجيل 6 أنواع من القشريات متماثلات الأرجل البرية منها 5 أنواع تسجل لأول مرة في سورية وهي: Armadillidium vulgare; ; Armadillo officinalis ; ;Porcellio laevis Porcellio scaber ،Porcelliondes pruinosus ; Ligia italica تم توصيف هذه الأنواع مورفولوجياً وربط وجودها مع أهم العوامل البيئية التي تؤثر على توزعها كدرجة الحرارة والرطوبة.